Sistem Pendukung Keputusan Pemilihan Bahan Makanan Bergizi Untuk Manula Menggunakan Metode Simple Additive Weighting ( Studi Kasus di Panti Jompo Laweyan ) - , Anshori; , Aris Rakhmadi, S.T., M. Eng (2016)
Elderly is natural process that accompained a decrease in the physical condition, psychological and social has the potential to cause health problems, both on general cases and specifically on the mental health of the elderly. The lack of nutrition will reflects a low physical quality and impact on the level of health condition. The purpose of this research is to ease users in selecting nutritious foods for elderly. This application use SAW methods (simple additive weighting). Aapplication use some benefit & cost criteria. The cost criteria is sex (male, female), and the benefit are (age 60-75, 75-90, >90), diseases (heart, uric, stroke, high blood), and alergics (fish, shrimp, duck, shells). The result of this research is an application that serve users to determine good foodstuff for elderly.